Stress-dependent scaling behavior of subcoercive field dynamic ferroelectric hysteresis in Pb (Zn13 Nb23) O3 -modified Pb (Zr12 Ti12) O3 ceramic - R. Yimnirun (2018)
Scaling behavior of subcoercive field dynamic ferroelectric hysteresis under influence of stress was investigated in Pb (Zn13 Nb23) O3 -modified Pb (Zr12 Ti12) O3 (PZT) bulk ceramic. The scaling relation of hysteresis area 〈A〉 against frequency f, field amplitude E0, and stress for the minor loops takes a form of 〈A- A=0 〉 f-0.42 E03.65 0.24, which is very similar to that of soft and hard PZT ceramics. However, slightly faster responses to f and E0 indicate the ease of polarization orientation in this simpler domain structure ceramic as compared to commercial PZT ceramics. © 2008 American Institute of Physics.